Analisis Strukturalisme Pada Cerpen "Gerobak" Karya Seno Gumira Ajidarma - Moh. Naufal Mufid; Bambang Hartanto (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
The short story "Gerobak" by Seno Gumira Ajidarma reflects the complexity of social inequality and the impact of structural poverty in urban society. Using a structuralism approach, this study analyzes the theme, plot, characters, setting, point of view, and moral message in this short story. The analysis reveals the coherence between intrinsic elements that provides a profound critique of social injustice and environmental degradation. This work highlights the importance of collective moral responsibility in creating social justice and maintaining environmental balance.